Stressed and Shopping: Examining Social Media-Induced Stress and Online Impulsive Buying in Gen Z - Sri Wiludjeng Sunu Purwaningdyah; Sri Astuti Pratminingsih (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
This study investigates how social media-induced stress influences online impulsive buying behavior among Gen Z consumers within a social commerce context. It further explores the mediating role of negative coping strategies and the moderating effect of self-control. Data was collected through online questionnaires targeting 300 Gen Z respondents selected via purposive sampling criteria, then analyzed using conditional process analysis with SPSS macro-PROCESS. Findings confirm that social media-induced stress, directly and indirectly, triggers impulsive buying through negative coping. Additionally, self-control significantly moderates this relationship, wherein lower self-control intensifies the effect of stress on impulsive buying. This research addresses gaps in the literature by highlighting the role of negative emotions, specifically stress, in driving consumer behavior. Findings contribute valuable insights into evolving digital consumerism patterns among Gen Z, emphasizing the need for self-control in digital environments while also highlighting how negative coping acts as the mechanism that channels stress into impulsive buying behavior.